Cytoskeleton Dynamics Methods and Protocols - Maiato, Helder (Methods in Molecular Biology, 2020)
This volume details comprehensive state-of-the-art methods on actin microfilaments and microtubules and how they work to achieve different cellular functions in different cellular contexts. Chapters guide readers through protein purification, in vitro reconstitution of several cytoskeleton properties, analyses of microtubule- and actin-based structures, functional dissection of post-translational modifications, and roles in several biological processes. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and cutting-edge, Cytoskeleton Dynamics: Methods and Protocols aims to provide a wide range of experimental approaches and be an invaluable resource for present and future generations of cytoskeleton researchers. The chapter "Visualization and Functional Analysis of Spindle Actin and Chromosome Segregation in Mammalian Oocytes" is available open access under a Creative Commons Attribution 4.0 International License via link.springer.com.